2008
DOI: 10.1073/pnas.0711626105
|View full text |Cite
|
Sign up to set email alerts
|

The nature of O 2 activation by the ethylene-forming enzyme 1-aminocyclopropane-1-carboxylic acid oxidase

Abstract: Ethylene is a plant hormone important in many aspects of plant growth and development such as germination, fruit ripening, and senescence. 1-Aminocyclopropane-1-carboxylic acid (ACC) oxidase (ACCO), an O 2-activating ascorbate-dependent nonheme iron enzyme, catalyzes the last step in ethylene biosynthesis. The O 2 activation process by ACCO was investigated using steady-state kinetics, solvent isotope effects (SIEs), and competitive oxygen kinetic isotope effects ( 18 O KIEs) to provide insights into the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 38 publications
4
77
1
1
Order By: Relevance
“…It is not definitively known whether this decomposition occurs at the active site or elsewhere (5). Bicarbonate has been identified as an essential mediator for proton transfer in the process (6)(7)(8). It remains unclear as to how the iron-containing active site of ACC oxidase is protected from the cyanide by-product, a known deactivating agent of iron-containing enzymes in general and Fe(III) in particular (9).…”
Section: Main Textmentioning
confidence: 99%
“…It is not definitively known whether this decomposition occurs at the active site or elsewhere (5). Bicarbonate has been identified as an essential mediator for proton transfer in the process (6)(7)(8). It remains unclear as to how the iron-containing active site of ACC oxidase is protected from the cyanide by-product, a known deactivating agent of iron-containing enzymes in general and Fe(III) in particular (9).…”
Section: Main Textmentioning
confidence: 99%
“…Number 1.14.17.4 refers to the enzyme aminocyclopropanecarboxylate oxidase. of ethylene, a hormone that plays an important role in different stages of plant growth and development such as the germination, maturation, and senescence of fruits (Mirica and Klinman, 2008). In tomato, ACC oxidase accumulates in various tissues during different stages of development and during leaf, fruit, and flower senescence (Barry et al, 1996).…”
Section: Genes Induced In the Sensitive Cultivarmentioning
confidence: 99%
“…The Fe2OG dioxygenases catalyze a variety of twoelectron oxidations, including hydroxylations, desaturations, and oxidative ring closures (Costas et al, 2004). Although the sequence homology among these enzymes is not high, all their active sites contain a single ferrous ion bound in a tridentate ligand arrangement referred to as a "2-His-1-carboxylate facial triad" (Mirica and Klinman, 2008). Secondary structure analysis of GbACO protein by SOMPA revealed that GbACO consists of α-helix (40.43%), β-turn (10.33%), extended strand (13.07%), and random coil (36.17%).…”
Section: Characterization Of the Deduced Gbaco Proteinmentioning
confidence: 99%
“…Under conditions of high ethylene production, the pathway can also be regulated at the level of conversion of ACC into ethylene by ACO (Vanderstraeten and Van Der Straeten, 2017). ACO enzyme belongs to the family of oxidoreductases which utilize Fe (II) as a cofactor and 2-oxoglutarases (2OG) as cosubstrate, although ACO uses ascorbate as a co-substrate (Prescott, 1993;Ryle and Hanusinger, 2002;Zhang et al, 2004;Mirica and Klinman, 2008). ACO needs bicarbonate as an activator and catalyzes the oxidation of ACC to give ethylene, CO 2 , and HCN.…”
mentioning
confidence: 99%